Islamophobia: Annihilator of Universal Declaration of Human Rights 1948 A Critique of Western States’ Policies - Dr. Muhammad Anas Rizwan; Dr. Usman Rafiq (MEI, 2023)
Islamophobia in western states is increasing and their governments openly or otherwise responsible for it. Policies of the western states that forbid the Muslims from carrying out their religious practices provoke the non-Muslims to adopt anti-Islam and anti-Muslimism attitude, which moves them towards hate, bias and prejudice against Muslims. The growth of prejudice becomes a reason for violation of human rights such as right of life, right of dignity and respect, right of equality, right of protection and security and freedom to practice self-religion. All these are in fact damaging United Nations Universal Declaration of Human Rights 1948. This article detects such Islamophobia and points out to direct and indirect endorsement of the western states governments for the growth of Islamophobia; the hate against Islam and Muslims. Further, the article establishes the linkage between Islamophobia and practical violations of human rights of Muslims. The article at the last, will critically analyze the western states’ policies with a slight touch of Islamic human rights teachings. It is hoped that the article will benefit the lawmakers and enforcement agencies to save their own societies. Keywords: Islamophobia, Hate, Bias, Prejudice, Human rights, Western States